2009
DOI: 10.1021/ja810107a
|View full text |Cite
|
Sign up to set email alerts
|

Template Trapping and Crystal Structure of the Magic Number (H2O)21 Cluster in the Tetrahedral Hole of a Nanoscale Global Ion Packed in a Face-Centered Cubic Pattern

Abstract: A nanoscale global ionic cluster [Co(H(2)O)(6) [symbol: see text] Co(8)L(12)](6+) packed in a face-centered cubic pattern was constructed as a "host", in which a magic number (H(2)O)(21) cluster was captured and stabilized in the tetrahedral hole as a "guest".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…It is known that the conning environment provides favorable condition for the formation of hydrogen bonded water clusters, whose structure is like solid ice, and it can be stable even at room temperature. [24][25][26][27][28] This type of hydrogen bonded water structure can be formed in the hydrophilic pore of Cu 3 BTC 2 . To verify how the conned water molecules exist in the pores of Cu 3 BTC 2 , we performed a Raman analysis on the OH-stretching vibration of water, which provides information about its dynamics.…”
Section: Resultsmentioning
confidence: 98%
“…It is known that the conning environment provides favorable condition for the formation of hydrogen bonded water clusters, whose structure is like solid ice, and it can be stable even at room temperature. [24][25][26][27][28] This type of hydrogen bonded water structure can be formed in the hydrophilic pore of Cu 3 BTC 2 . To verify how the conned water molecules exist in the pores of Cu 3 BTC 2 , we performed a Raman analysis on the OH-stretching vibration of water, which provides information about its dynamics.…”
Section: Resultsmentioning
confidence: 98%
“…For the synthesis of the ligand, see: Wieprecht et al (2005). For complexes based on the ligand, see: Cao et al (2008Cao et al ( , 2009.…”
Section: Related Literaturementioning
confidence: 99%
“…Although coordination chemistry of the symmetrical ligands like TPT has been well explored, the observations on the asymmetric ligands containing triazine ring are still rare. As a contribution to the synthesis and structural studies of coordination abilities of 4,6-bis(2pyridyl)-1,3,5-triazin-2-ol ligand (Wieprecht et al, 2005;Cao et al, 2008Cao et al, , 2009, I present here the crystal structure of the title compound (…”
Section: Sup-1mentioning
confidence: 99%
“… 5 8 For example, Cao et al recently reported a study of template trapping and crystal structure of the magic number (H 2 O) 21 cluster in the tetrahedral hole of a nanoscale global ion packed in a face-centered cubic pattern. 9 Other experimental studies have explored the confinement and stabilization of condensed-phase water clusters within other predesigned hosts, such as organic materials, 10 inorganic microporous materials 11 , 12 and metal–organic frameworks. 13 – 18 Such studies, in general, can provide insight into the structure and behavior of condensed-phase water clusters that otherwise cannot be discretely isolated.…”
Section: Introductionmentioning
confidence: 99%